Radiation-Induced Change in Lymphocyte Proliferation and its Neuroendocrine Regulation: Dose-Response Relationship and Pathophysiological Implications - Shu-Zheng Liu (SAGE Publishing, 2004)
Cellular activities are regulated by intracellular signals initiated by stimulation from the external and internal environments. Different signal pathways are involved in the initiation of different cellular functions. In connection with cell proliferation in response to mitogenic stimulation, the dose-effect relationship of the magnitude of H-TdR incorporation into lymphocytes after exposure to different concentrations of concanavalin A (Con A) showed an inverted U-shaped curve in the concentration range 2-30 μg/ml. In previous studies it has been observed that the stimulatory effect of Con A (5 μg/ml) on lymphocyte proliferation was potentiated by whole-body irradiation (WBI) with low dose (0.075 Gy) and suppressed by WBI with high dose (2 Gy). When different concentrations of corticosterone, ranging from 10 −12 to 10 −7 M, were added to the Con A-stimulated lymphocytes, low-concentration stimulation and high-concentration suppression of lymphocyte proliferation were demonstrated. In the presence of 5 × 10 −12 M (subphysiological concentration) of corticosterone the proliferation of thymocytes and splenic T cells in response to Con A was further up-regulated after low-dose radiation. Low-dose radiation (0.075 Gy) caused lowering of serum ACTH and corticosterone concentration as well as down-regulated transcription of the hypothalamic proopiomelanocortin gene. The present paper intends to show that multiple neurohormonal factors, including the pineal gland and neurotransmitters, in addition to the hypothalamic-pituitary-adrenocortical axis, are involved in the stimulation of immune responses induced by low-dose ionizing radiation. The complex nature of the interrelationship between the intracellular signaling of lymphocytes and the neuroendocrine regulation after WBI is discussed.